After Bali : the threat of terrorism in Southeast Asia - Workshop on "After Bali: the Threat of Terrorism in Southeast Asia" (2003 : Singapore); Ramakrishna, Kumar; Tan, See Seng, 1965- (Singapore ; River Edge, N.J. : World Scientific ; Singapore : Institute of Defence and Strategic Studies, 2003)
This book critically analyses the specific threat of terrorism in Southeast Asia since the Bali blasts of 12 October 2002 and the US-led war on Iraq. It offers a comprehensive and critical examination of the ideological, socioeconomic and political motivations, trans-regional linkages, and media representations of the terrorist threat in the region, assesses the efficacy of the regional counter-terror response and suggests a more balanced and nuanced approach to combating the terror threat in Southeast Asia.
Copyright; Acknowledgements; Foreword; Contents; List of Contributors; Introduction; 1 -- Bali and Southeast Asian Islam: Debunking the Myths; 2 -- Deconstructing Jihad: Southeast Asian Contexts; 3 -- The Question of "Links" Between Al Qaeda and Southeast Asia; 4 -- The Indigenous Roots of Conflict in Southeast Asia: The Case of Mindanao; 5 -- Understanding Al Qaeda and its Network in Southeast Asia; 6 -- Al Qaeda in Southeast Asia: Exploring the Linkages; 7 -- The Globalised Media and Southeast Asia: Boon or Bane?; 8 -- Evaluating Western Meia Perceptions of Thailand After the Bali Bombing.
"Workshop entitled "After Bali:The Threat of Terrorism in Southeast Asia", held in Singapore between 27and 28 January 2003"--Foreword
Includes bibliographical references (pages 403-419) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Terrorism -- Southeast Asia -- Congresses; Terrorisme -- Asie du Sud-Est -- Congrès.; SOCIAL SCIENCE -- Violence in Society; Terrorism; Southeast Asia; Conference papers and proceedings